Oral Manifestations in Patients with Down's Syndrome and Management in Prosthodontics - Achmad Syawqie; Jennifer Putri; Stephanie Yessica; Nuroh Najmi (Jurnal EduHealth, 2023)
Down syndrome is an autosomal disorder associated with involving mental and physical changes. The types of craniofacial phenotypes and dental anomalies in individuals with Down syndrome have been described extensively, but further elaboration of their impact of oral and craniofacial conditions still needs to be understood. In addition, in prosthodontic, oral rehabilitation with complete dentures and implants in patients with Down's syndrome still needs to be studied. The aim of this review is to describe that the oral and craniofacial manifestations may occur in patients with Down syndrome, and determine the effectiveness of oral rehabilitation treatments in patients with Down syndrome. The article was   conducted of two databases and were limited to the period from January 2016 to February 2022 with a combination of the following keywords: “Down Syndrome”, “oral manifestation”, “implant”, “prosthodontic treatment”. The results obtained were 194 articles found at the beginning of the search in both databases, and the 16 full text articles were selected for further review and discussion. The results of this study shows that Down syndrome causes several oral and craniofacial manifestations, dental caries risk, higher periodontal disease, dental abnormalities, soft and occlusal tissue, and the presence of a craniofacial complex. In prosthodontics, the choice of using removable dentures or implants must be adjusted to each patient's condition. Down syndrome is an autosomal disorder that has oral and craniofacial manifestations that must be a concern for health practitioners, especially dentists. In prosthodontics, oral rehabilitation with either complete dentures or implants in patients with Down's syndrome is the right choice, but it is necessary to consider the complications that may occur.